The building of a research problem: women as victims of the armed conflict (2019)
This paper aims to build some clues to critically reflect on the construction of the research problem “women as victims of the armed conflict,” This problem is constructed considering the dimension of the scientific research, but also the political and social dimension that it implies. Therefore, it is assumed that every problem has a social research historicity in which different actors have participated in its construction. For this case, the State, NGOs, international organizations and Human Rights organizations have contributed in the way victim womanhood is performed. Therefore, what matters is to problematize this construction and analyze the social and political implications that it generates.